Understanding Cardiotocography: Technical Aspects - C. Tolcher, Mary; D. Traynor, Kyle (Current Women's Health Reviews, 2013)
Electronic fetal monitoring (EFM) via cardiotocography was introduced into clinical practice over four decades ago. The intent of fetal monitoring is secondary prevention and early recognition of fetal compromise, including hypoxia and acidosis, so that fetal death can be prevented. Clinical research has failed to show that EFM improves neonatal outcomes including cerebral palsy and has not been shown to be superior to intermittent auscultation. Moreover, EFM is associated with increased rates of operative delivery. Despite the shortcomings of this method of fetal assessment, the use of cardiotocography is widespread in clinical practice. Though largely unchanged in recent decades, a basic understanding of the technology involved in the collection and analysis of the monitoring data is necessary for clinicians to be able to interpret and intervene when indicated. The objective of this review is to provide an overview of basic concepts and technical aspects of commonly employed methods of fetal monitoring.
Keywords: electronic fetal monitoring